Filmes e revestimentos antimicrobianos de proteínas miofibrilares a partir de subprodutos de Tilápia (Oreochromis niloticus) com aplicação em postas de Cavala (Scomberomorus cavalla) - Leite, Lana Oliveira (2018)
Processing waste is also one of the main obstacles in the fishing industry due to waste and the environmental impact of generating properties. In this way, several forms of reutilization are researched with the objective of generating new products with different applications from agroindustry residues. The objective of this work was to develop and evaluate antimicrobial films and coatings of proteins obtained from mechanically separated meat (CMS). For this purpose, myofibrillar proteins of tilapia (Oreochromis niloticus), glycerol and lactic acid were used. The amino acid profile of the myofibrillar protein sample of Nile tilapia was characterized and the highest concentrations present are aspartic acid (12.05 ± 0.05%), glutamic acid (12.18 ± 0.04%), lysine (10.42 ± 0.04%) and proline (8.92 ± 0.09%). In order to obtain the films it was used the casting technique in which several experiments were carried out, varying the composition of the film-forming solution in relation to the amount of protein (1%, 1.5% and 2%) and glycerol (0.0% 0.1%, 0.2%). The films were characterized in terms of color and opacity, water solubility, mechanical properties and water vapor permeability (PVA). The filmogenic solutions of these films were used as protein coating (PR) by dipping technique to evaluate the wetting or scattering capacity (Ws) on the surface of mackerel (Scaberulous cavalla) and the highest Ws was the coating of 1% of protein and 0.1% glycerol. The antimicrobial activity of the coatings, in relation to Escherichia coli, Staphylococcus coagulase positive, Salmonella Enteritis’s and Vibrio pahaemolyticus, was verified by the well diffusion method. The coatings at the minimum concentration of 1% (RP) were those that developed better antimicrobial activity in relation to the evaluated microorganisms. The film-forming solution of 1% PB and 0.1% glycerol was used as coating by dipping technique to evaluate changes in fresh and frozen mackerel (Scaberulous cavala) slates at -18 ± 3 ° C for 180 days. It was evaluated characteristics such as weight loss, glaciation and coating, pH, N-BVT, TBARS and microbiological growth of psychotropic bacteria at 7ºC. In all treatments, where mackerel was coated with protein solutions, the results were better than the treatment control and the treatment of glaciation which is a practice already allowed in legislation. The treatments were divided into control (C), glacier (G) and protein coating (RP), which contained in its formulation 1 g of myofibrillar protein and 0.1 mL of glycerol, because it is the film-forming solution which presented the best result in all analyzed characteristics.